A quality improvement approach in co-developing a primary healthcare package for raising awareness and managing female genital schistosomiasis in Nigeria and Liberia. (24th March 2023) - Oluwole, Akinola S; Bettee, Anthony K; Nganda, Motto Malea; Piotrowski, Helen L; Fapohunda, Victoria O; Adejobi, Josephine B; Soneye, Islamiat Y; Kafil-Emiola, Maryam A; Soyinka, Festus O; Nebe, Obiageli J; Ekpo, Uwem F; Kollie, Karsor K; et al.
Abstract: Background: Girls and women living in endemic areas for urogenital schistosomiasis may have lifelong vulnerability to female genital schistosomiasis (FGS). For >2 decades, the importance of FGS has been increasing in sub-Saharan Africa, but without established policies for case detection and treatment. This research aimed to understand the level of FGS knowledge of frontline health workers and health professionals working in endemic areas and to identify health system needs for the effective management of FGS cases and prevention of further complications due to ongoing infections. Methods: Workshops were conducted with health workers and stakeholders using participatory methods. These workshops were part of a quality improvement approach to develop the intervention. Results: Health workers' and system stakeholders' knowledge regarding FGS was low. Participants identified key steps to be taken to improve the diagnosis and treatment of FGS in schistosomiasis-endemic settings, which focused mainly on awareness creation, supply of praziquantel, development of FGS syndromic management and mass administration of praziquantel to all eligible ages. The FGS intervention component varies across countries and depends on the health system structure, existing facilities, services provided and the cadre of personnel available. Conclusion: Our study found that co-developing a new service for FGS that responds to contextual variations is feasible, promotes ownership and embeds learning across health sectors, including healthcare providers, NTD policymakers and implementers, health professionals and community health workers.